An analytical review of Valentine's Day in the light of Quran and Sunnah: ویلنٹائن ڈے کا قرآن و سنت کی روشنی میں ایک تجزیاتی جائزہ - Anjum, Dr. Khawar; Akram, Noor; Hubshi, Prof. Dr. Abdul Latif (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Valentine's Day is celebrated on 14th February every year. It is also called the festival of love. In Europe on this day people express their love to their beloved and spend time together. The general procedure for this expression is that roses are handed to the beloved with a romantic message or deed. Some people also choose this day to express their love for the first time or to propose for marriage. The purpose of this behavior is to make his propose memorable. Some people also use unique methods for this, such as expressing their love to their beloved on a billboard or hanging a message poster with a bunch of flying balloons. It was introduced in Pakistan from the nineties. Initially, only the rich families were affected by it, but at the beginning of the 21st century, it was widely discussed in the media. Religious parties opposed it. In contrast, some people introduced Haya Day. While a university administration also suggested celebrating Sisters' Day on this occasion. It was widely opposed in India as well and was considered an attack on Indian culture, while some Hindu organizations suggested to show love to the cow in that day. In this article we will try to find answers to some questions in view of the Qur'an and Sunnah, regarding Valentine's Day: e.g. what is Valentine's Day? How did it start? When was Valentine's Day introduced in Pakistan? And is making love forbidden in Islam? Also, is there any flaw in "apart from appointing a separate day"?